Interferons as Neoadjuvant Chemotherapy for Giant Cell Tumor: A Hospital-Based Prospective Pilot Study - Sah, Saroj Prasad; Regmi, Anil; Niraula, Bishwa Bandhu; Sehrawat, Amit; Bhagat, Saroj Kumar; Dhingra, Mohit (Indian Journal of Medical and Paediatric Oncology, 2024)
Introduction Neoadjuvant chemotherapy is now considered an effective way to treat Campanacci grade 2 and 3 giant cell tumors (GCTs). Assessment of these drugs is essential clinically, radiologically, and pathologically. This study analyzes the early results of angiogenesis inhibitors (interferons) in the aggressive GCT of bone.Methodology A prospective pilot study was conducted from January 2021 to July 2022 including eight biopsy-proven GCT patients subjected to interferon therapy. Radiological assessment was done with changes on plain radiograph, computerized tomography scan, and magnetic resonance imaging. Histopathological examination was done by changes in the biopsy and resected segment.Results Out of the eight patients included in the study, 26% (n = 3) were males and 62% (n = 5) were females, with mean age of the patients being 24.6 ± 8.48 years (range: 22–38). There was significant reduction of the size of swelling (p-value: 0.049), significant reduction in Visual Analog Scale score (p-value: 0.011), significant decrease in swelling size on radiograph (p-value: 0.012), significant marginal sclerosis (p-value: 0.001), significant neocortex formation on radiographs (p-value: 0.001), significant result in and osteoid formation (p-value: 0.001) on histology. Whereas Campanacci grade on plain radiographs, number of viable cells, and number of viable stromal cell were not statistically different in comparison with pretherapy and posttherapy status.Conclusion Interferon therapy in a GCT has potential beneficiary effect in terms of clinical, radiological, and pathological outcomes. It might prove to be an effective alternative to standard neoadjuvant chemotherapy in the management of aggressive GCT of bones.Level of Evidence III.
Keywords: giant cell tumor; neoadjuvant chemotherapy; interferon; Campanacci grading; ICDS criteria; RECIST criteria